Biological affinities of Brazilian pre-colonial coastal communities explored through bootstrapped biodistances of dental non-metric traits. (February 2022) - Fidalgo, Daniel; Wesolowski, Veronica; Hubbe, Mark
Abstract: Based on dental morphology, it was recently suggested that the Southeast Coast of Brazil was inhabited by different biological groups throughout the Holocene. Among those that inhabited São Paulo state, coastal shellmound builders seem biologically distant from riverine shellmound builders. Additionally, individuals that later built ichthyological sites are also biologically distant from both early coastal or riverine populations. However, mainly due to low sample sizes, such conclusions may not be reliable, and require further inquiry. Here, we explore the confidence interval of biological affinities among five archaeological series (Piaçaguera, Buracão, Tenório, Mar Virado and Moraes), composed by 128 individuals from different chronological and archaeological backgrounds. We use a bootstrapping analysis of biodistances, which illustrates the expected error that results from sample sizes, by generating density estimations based on the observed biological affinities among series. Our results contradict previous claims based on dental analyses by showing that individuals from ichthyological sites cannot actually be considered distinct from Southeast coastal and riverine shellmound builders. On the other hand, it shows that early coastal and riverine shellmound builders are not biologically related, thus supporting prior assumptions of high phenotypic variation among Southeast shellmound builders, at least within the scope of São Paulo state. Finally, although shellmound builders are related to individuals from ichthyological sites to some extent, early and later coastal shellmound builders of this area do not appear to be biologically related, which further highlights the complex dynamics of population movement in the area. Highlights: Bootstrap method to evaluate biodistances using non-metric variables. Higher phenotypic variation among shellmound builders. Lower phenotypic variation among individuals from ichthyological sites.